Intelligent tutoring systems in e-learning environments : design, implementation, and evaluation - Stankov, Slavomir, 1947-; Glavinic, Vlado, 1952-; Rosic, Marko, 1970- (Information Science Reference, 2011)
"This book addresses intelligent tutoring system (ITS) environments from the standpoint of information and communication technology (ICT) and the recent accomplishments within both the e-learning paradigm and e-learning systems"--Provided by publisher.